Effects of compatibilizer type and rubber-wood sawdust content on the mechanical, morphological, and thermal properties of PVC/LDPE blend - Prachayawarakorn, J.; Khamsri, J.; Chaochanchaikul, K.; Sombatsompop, N. (My University, 2006)
This article aimed to investigate the mechanical, morphological and thermal properties of PVC/LDPE blend with and without the addition of compatibilizers. The effects of LDPE content, compatibilizer type and rubberwood sawdust loading on the properties of the blend were evaluated. The experimental results suggested that as the LDPE content was increased the mechanical properties of PVC-LDPE blend progressively decreased due to poor interfacial adhesion. The continuity and compatibility between PVC and LDPE phases could be improved through three different types of compatibilizers which included chlorinated polyethylene (CPE) poly(methyl-methacrylate-co-butyl acrylate) (PA20) and poly(ethylene-co-methacrylate) (Elvaloy). The PA20 was found to be the most suitable compatibilizer for the blend. A radical transfer reaction was proposed in this work to explain the structure and thermal changes of the PVC in PVC-LDPE blend. The decomposition temperature of PVC in the blend decreased with the loading of the PA20 and the wood sawdust. As the sawdust content was increased the tensile and flexural moduli increased with considerable decreased in the tensile, flexural and impact strength, a slight improvement being achieved if the PA20 was incorporated in the composite. © 2006 Wiley Periodicals, Inc.
Keywords: Composite; Mechanical properties; Poly(vinyl chloride); Polymer blend; Wood sawdust